Students' Mathematical Literacy Processes on PISA-Like Tasks with The Domain of Space and Shape - Pradnya Paramitha Solikhah; Endah Budi Rahaju; Nina Rinda Prihartiwi (MATHEdunesa, 2022)
Mathematical literacy is defined as the ability possessed by an individual in formulating, employing, and interpreting mathematics in a variety of contexts. This research aims to describe the mathematical literacy processes of Junior High School students in solving PISA-like problems on space and shape content. The method in this research used qualitative descriptive. The research subject was students of the ninth grade in SMP Negeri 2 Krembung on Sidoarjo, which consisted of twenty-nine students. The instruments used were test and interview. The results showed that the students’ mathematical literacy was classified as less for the process of formulating. Some students still find many difficulties, such as difficulty in determining the strategy used in solving the problem as well as errors in calculation and drawing conclusion. The students’ mathematical literacy was classified as quite good for the process of employing. Students understand the intent of the problem and know what strategy used, although there were some minor errors in calculation or drawing a conclusion. The students’ mathematical literacy was classified as very lacking in the process of interpreting. Students only guess because students were still unable to understand the meaning of the questions and what strategies were used to solve the given problems to answer questions.